Concentração do mercado de educação superior no Brasil: uma análise do efeito das fusões e aquisições sobre o desempenho acadêmico - Spolavori, Rafael (Universidade do Vale do Rio dos Sinos, 2016)
This study analyzes the effects of mergers and acquisitions in the Brazilian private higher education sector on quality and academic performance of the higher courses of Business Administration, Law and Pedagogy. The methodology is divided in two stages; first, the PSM (propensity score matching) was obtained in order to geet the common support; then, we estimated the acquisition effect using the difference-difference method. As to the analysis of the acquisition effects, the results indicate a higher proportion of PhD professors in the Business Administration and Pedagogy courses, and a higher proportion of professors with Master’s degree in the Business Administration course. The Preliminary Course Concept (PCC), the average of the graduating students in the Nacional Student Performance Exam general education test and the average of the graduating students in the Nacional Student Performance Exam specific knowledge test did not present significant effects with the acquisitions. The General Course Index (GCI) of the acquired Higher Education Institutions (HEI) did not have significant effects with the acquisitions either. These results indicate that the analysis of the effects of mergers and acquisitions is still incipient and should be continued with the dissemination of new and updated quality indicators.
Keywords: Ensino superior; Qualidade; Fusões e aquisições; Higher education; Quality; Mergers and acquisitions; ACCNPQ::Ciências Sociais Aplicadas::Economia